2015
DOI: 10.1007/s12257-015-0258-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic proteome and its network response to supplementation of an anti-obesity herbal mixture in diet-induced obese mice

Abstract: In the present study, we investigated the effects of multi-herbal water extract mixture, Taeumjowi-tang (TH) on liver proteome alteration in mice using twodimensional electrophoresis combined with MALDI-TOF-MS. Animals were fed high-fat diet with or without TH (0.3% wt/wt) supplement for 12 weeks. At the end of 5 th week of experimental diet, mice fed high-fat diet only were subdivided into 2 groups, obesity-prone (OP) and obesityresistant (OR) mice based on weight gain. OR mice gained less body weight compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Taeumjowi-tang is a popular herbal product in Korea and is generally used for weight loss [6][7][8][9][10]32] and changes in several lipid profiles [6,11,13,14]. Until now, there have been no studies reporting prediction models or algorithms for the efficacy of Taeumjowi-tang or other herbal medicines for an individual.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Taeumjowi-tang is a popular herbal product in Korea and is generally used for weight loss [6][7][8][9][10]32] and changes in several lipid profiles [6,11,13,14]. Until now, there have been no studies reporting prediction models or algorithms for the efficacy of Taeumjowi-tang or other herbal medicines for an individual.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have examined the efficacy of Taeumjowi-tang. To examine the association of oral administration of Taeumjowitang with anthropometric and blood parameters, many studies have proven that the efficacy of Taeumjowi-tang is useful for weight reduction or changes in lipid profiles in humans and mice [6][7][8][9][10][11][12][13][14]. For example, Yoo et al [6] examined changes in anthropometric indices and blood parameters after dose intake of Taeumjowi-tang in obese Korean children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another anti-obesity herbal medicine Taeumjowi-tang (TH) consisting of eight herbs has traditionally been used in Korea. Kim et al [40] identified the proteins differentially expressed in hepar of TH-treated obesity model rats utilizing proteomic and western blot analysis, and deduced that TH improved lipid metabolism through modulating fatty acid metabolizing proteins involved in obesity and hepatic injury, with the involvement of adenosine monophosphate-activated protein kinase, acetyl CoA carboxylase and fatty acid synthetase.…”
Section: Differential Proteomics For Exploring the Action Mechanisms mentioning
confidence: 99%